Investigation of severity of head impact in fall due to collisions - Chua, Yih Fan (2019)
With the increase in the use of PMDs, PABs and bicycles more accidents are happening in Singapore. PMD related accident alone has increased to more than 1300 cases from 2018. Government’s effort and current solution might be insufficient to reduce the accident. In this report, the author will investigate the effects of various factor namely, surface of impact, impact velocity and drop height on HIC. A drop test experiment set up was designed to meet the objective set out for this project. Literature review were done on HIC and past experimental methods used by other institutes or researchers. In this project the DTS Headsafe Impactor is the main equipment utilized to record the data from the drop tests. The data collected are analysed using the TSR Control software. From the results obtained from the analysis, dropping the Headsafe Impactor on different type of surfaces at different speed produces different HIC values. In conclusion the objectives for this project was achieved. The results obtained will be useful for organization like the LTA. Recommendation for further development of this project was also given.